Selected state policies and associations with alcohol use behaviors and risky driving behaviors among youth: Findings from the Monitoring the Future study - Cavazos-Rehg, Patricia A. (Alcohol Clin Exp Res, 2016)
BACKGROUND: Effective policies that can reduce alcohol use behaviors and impaired driving among young people at a population-level are needed. Graduated driver licensing (GDL) laws increase the driving privileges of young novice drivers as they age and gain more driving experience. In this study we seek to determine the effects of GDLs on risky driving behaviors of youth and to assess if GDLs have an unintended effect on underage drinking behaviors. METHODS: We utilized 2000-2013 data on 12(th) grade students from the Monitoring the Future (MTF) study, an ongoing, annual national survey (since 1975) that studies the substance use behaviors of adolescents, as well as data on GDL laws obtained via the Insurance Institute for Highway Safety (IIHS). We conducted a series of regular logistic regression models that included fixed effects for year and state, and adjusted for demographic characteristics, school characteristics, and other state alcohol policies. RESULTS: Total weighted sample size was 129,289 12(th) graders. Past month alcohol use and binge drinking (i.e., ≥5 drinks on one occasion) in the past two weeks were 45% and 26%, respectively. Seventeen percent of respondents reported riding with a driver who drank alcohol. Nearly 12% reported driving in the past two weeks after drinking alcohol, and 7% reported driving after binge drinking. Over half of students lived in a state with a “good” GDL law. The logistic regression models suggest a link between restrictive GDL policies and a reduction of alcohol use behaviors and risky driving behaviors among youth. CONCLUSIONS: Our findings indicate that the effects of GDLs extend beyond driving-related risks and into other drinking-related behaviors that pose immediate or delayed health risks for young people. We speculate that GDLs may dictate social norms and expectations for youth risk behaviors, and should be maximized throughout the U.S.